Recourir à la musique pour favoriser le bien-être et l’intégration des personnes réfugiées à Québec - Arsenault, Stéphanie; Moreno Sala, Maria (Nouvelles pratiques sociales, 2020)
Cet article porte sur une intervention musicale et interculturelle de groupe qui visait l’amélioration du bien-être psychologique et l’intégration des personnes réfugiées dans la ville de Québec. L’expérience a regroupé 20 personnes, dont 10 Québécois de longue date et 10 personnes réfugiées nouvellement arrivées, qui se sont réunies à 10 occasions pour échanger et jouer de la musique ensemble. Les propos recueillis avant, pendant et après la démarche démontrent que l’activité a contribué à l’amélioration du sentiment de bien-être des réfugiés, mais aussi d’une majorité des Québécois de longue date. Les propos montrent que la démarche a aussi contribué à l’intégration des réfugiés.
Keywords: Quebec; Québec; integration; intervention sociale; intégration; music; musique; refugee; réfugié; social intervention

“Maple Leaf Rag” in Maple Leaf Country: Impressing Jazz upon Vera Guilaroff - Blais-Tremblay, Vanessa (Women and Music: A Journal of Gender and Culture, 2020)

Bïa Krieger versionista: Três cançoes de Chico Buarque em francês [Bïa Krieger, versionista. Trois chansons de Chico Buarque en français] - Cassiano, Raissa Conde (Université de São Paulo, 2020)

Mapping as a Complementary Perspective on the Dynamics of Participation in a City’s Musical Life - Marcoux-Gendron, Caroline; De Alvarenga, Bernardo (Bulletin of Sociological Methodology/Bulletin de Méthodologie Sociologique, 2020)
Maps and map-making have been used in a range of research about musical phenomena in cities. Yet, most of these studies focus on musicians; few have attempted to understand how people take part in a city’s musical life in terms of event attendance. Likewise, little has been said about the attendance habits of immigrants, despite the quick transformation of urban populations due to the expansion of human migration. Approaching a subject that has received so little attention as the dynamics of participation of immigrants in a city’s musical life therefore requires an inventive research design. Building from a methodology combining semi-structured interviews and observation, I used maps and map-making to deepen the analysis of North African immigrants’ cultural practices in Montreal. Trying to give a spatial legibility to their musical activities in the city generated many technical and theoretical concerns, but was also helpful for reflecting on the project differently and highlighting some characteristics of the data that were not obvious from the initial fieldwork. In brief, maps and map-making proved to be efficient complementary tools to ethnography, bringing new insights and raising new queries about the practices being considered.
Keywords: audiences; cartes; cartographie; cities; cultural participation; cultural practices; ethnographie; ethnography; immigration; map-making; maps; music; musique; participation culturelle; pratiques culturelles; publics; villes